GAMBARAN PENGETAHUAN DAN MOTIVASI IBU TENTANG PEMELIHARAAN GIGI TERHADAP STATUS KESEHATAN GIGI BALITA DI DESA GUNUNG TINGGI KECAMATAN PANCUR BATU KABUPATEN DELI SERDANG - Rawati Siregar; Sri Junita Nainggolan; Nurhamidah; Netty Jojor Aritonang (Poltekkes Kemenkes Medan, 2024)
Dental and oral health have a great role in human life. Tooth is also related to one’s body health especially in food processing. This study is aimed to determine the description of knowledge and motivation of mothers towards dental care of children Gunung Tinggi Village, Village III Sub District Pancur Batu Sub District Deli Serdang District. The type of this research is descriptive research with survey method . The data were collected by using questionnaires finding out the description of knowledge and motivation of mothers towards dental care of children aged 1-5 years. The sample of this research were 30 mothers and children in Gunung Tinggi Village, Dusun III Pancur Batu Sub District, Deli Serdang District. The results of this study indicate that the knowledge of 10 mothers (33.3%) is in good category, and 20 people (66.7%) are in moderate category, and there was no mother in poor category. Based on mothers’ motivation, 22 peoples (73,3% ) were in good criteria, 8 people (26.7%) were in moderate criteria, and no mother with poor criteria. Based on dental health status,10 people (33,3%) had caries and 20 people (66,7%) had no caries. The results showed that the level of knowledge and motivation is very influential towards the dental care among the children. It is expected that mothers put effort to maintain the dental health of their children by guiding the children to good and proper dental health care.